Variable Virulence Genes in Clinical Isolates of Burkholderia pseudomallei: Impact on Disease Severity and Outcome in Melioidosis - Raj, Sruthi; Sistla, Sujatha; Sadanandan, Deepthy Melepurakkal; Peela, Sreeram Chandra Murthy (Journal of Laboratory Physicians, 2023)
Objectives To isolate Burkholderia pseudomallei from clinical specimens and study the association of virulence genes with clinical manifestations and outcome in patients with melioidosis.Materials and Methods Burkholderiapseudomallei isolates obtained from melioidosis cases diagnosed during 2018 to 2021 were identified using VITEK 2 system and confirmed by polymerase chain reaction (PCR) targeting a Type III secretion system gene cluster. Multiplex PCR was performed to detect the genotypes of lipopolysaccharide (LPS) namely A, B, and B2, and singleplex PCR was performed to detect the presence of the Burkholderia intracellular motility gene (BimA) and filamentous hemagglutinin gene (fhaB3).Statistical Analysis Chi-square/Fisher's exact tests were performed to study the association between various clinical manifestations and outcome and different virulence genes. The results were expressed as unadjusted odds ratios with 95% confidence intervals.Results Sixty-seven isolates were available for characterization. BimABm and BimABp were observed among 82 and 18% of the isolates, respectively. Both sepsis and mortality were significantly associated with BimABm. Majority of the isolates had fhaB3 (97%). Most of the isolates showed the presence of LPS A gene (65.7%) followed by LPS B gene (6%), while LPS B2 was not detected. Nineteen isolates could not be assigned to any LPS genotypes.Conclusion Among the virulence genes studied, only BimABm was significantly associated with sepsis and mortality. More than a quarter (28.3%) of the isolates could not be assigned to any LPS genotypes, hinting at a greater genetic diversity in our isolates.
Keywords: Burkholderia pseudomallei; melioidosis; virulence genes